MEMBANGUN FIQH EKOLOGI BERBASIS MASLAHAH - Rahwan Rahwan (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2016)
Talking about the environment, it means talking about the environment around us, covering the entire ecosystem. Environment consists of flora and fauna, biotic and abiotic (and inanimate objects). Life environment are interdependent with each other. Human small part of the environment. This environment will determine the fate of human life. Will provide a conducive environment and secure quality of life, on the contrary, if the environment is less conducive it will result in insecure or lacking in quality even really threaten the safety of humans and the entire ecosystem in the world. Fiqh as Islamic law governing the pattern of human relationships with God and neighbor, and also discuss the human relationship with the environment. The share issue fiqh in an effort to maintain harmonious environment by providing rules or code of ethics of human relationships with the environment. As the ban on harming the environment and the obligation of preserving the environment. This environmental management is based to the proposition - proposition tipsily, namely al-Qur'an, al-Hadith, and the general principles of law legeslasi. When fiqh took part in preserving the environment, then the whole mukallaf particular awareness of environmental issues related to land, air and sea. So they have a high concern for the environment. Giving rights owned by the environment, such as the right to life and the right to expand, not plunder and exploit. With so environment remain stable, beautiful and conducive. Along with other human beings be peaceful. Based on the above views of researchers seeks to conduct research in matters of environmental jurisprudence. With the aim of formulating a comprehensive environmental fiqh, systematic, and akuntebel and can deal with the issue of global warming.